2020
DOI: 10.1021/acsnano.9b08320
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Grafted Magnetic Nanorings Mediated Magnetothermodynamic Therapy Favoring Reactive Oxygen Species-Related Immune Response for Enhanced Antitumor Efficacy

Abstract: In this study, a magnetothermodynamic (MTD) therapy is introduced as an efficient systemic cancer treatment, by combining the magnetothermal effect and the reactive oxygen species (ROS)-related immunologic effect, in order to overcome the obstacle of limited therapeutic efficacy in current magnetothermal therapy (MTT). This approach was achieved by the development of an elaborate ferrimagnetic vortex-domain iron oxide nanoring and graphene oxide (FVIOs-GO) hybrid nanoparticle as the efficient MTD agent. Such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
134
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(144 citation statements)
references
References 46 publications
1
134
0
Order By: Relevance
“…[ 59 ] PDT has been demonstrated to induce immunogenic cell death (ICD) and activate an adaptive immune response against tumor‐associated antigens. [ 60 ] As PDT is a typical oxygen‐consuming process whose effect can be severely limited by tumor hypoxia, thus the oxygen supplied nanoparticles can elicited ICD upon abundant ROS in PDT. Similarly, PTT has been shown to trigger the thermal ablation‐induced tumor ICD and cause the release of tumor antigens and endogenous adjuvants (e.g., heat shock proteins and damaged‐associated molecular patterns) to stimulate the immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…[ 59 ] PDT has been demonstrated to induce immunogenic cell death (ICD) and activate an adaptive immune response against tumor‐associated antigens. [ 60 ] As PDT is a typical oxygen‐consuming process whose effect can be severely limited by tumor hypoxia, thus the oxygen supplied nanoparticles can elicited ICD upon abundant ROS in PDT. Similarly, PTT has been shown to trigger the thermal ablation‐induced tumor ICD and cause the release of tumor antigens and endogenous adjuvants (e.g., heat shock proteins and damaged‐associated molecular patterns) to stimulate the immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species (ROS), which include hydroxyl radicals, superoxide, and hydrogen peroxide, can be produced by enzymatic and mitochondrial sources in normal and tumor cells [ 30 , 31 ]. If they continue to accumulate in cytoplasm and mitochondria, they may cause oxidative damage to proteins, DNA, RNA, and organelles [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…designed a graphene oxide (GO)‐grafted ferrimagnetic vortex‐domain iron oxide nanoring (FVIOs) nanohybrid and conjugated it with Cys‐Arg‐Glu‐Lys‐Ala (CREKA) peptide to improve tumor accumulation ( Figure a). [ 132 ] Such FVIO‐GO‐CREKA nanocomposites exhibited high magnetic thermal conversion efficiency and amplified ROS generation via a thermal‐enhanced Fenton reaction under AMF. The nanocomposite‐induced magnetothermodynamic therapy was able to provoke ICD, boost macrophage polarization to tumoricidal M1 phenotypes, and elevate the tumor‐infiltrating T lymphocytes in TME (Figure 14b).…”
Section: Htt‐based Multipronged Approaches In Synergistic Immunotherapymentioning
confidence: 99%
“…Inhibited bilateral tumor growth [128] MHT, CDT FVIO, graphene oxide Induced by PTT and ROS Not applicable 4T1 Inhibited tumor growth [132] MHT, PDT Some studies have demonstrated that some nanoparticles have potential risks; for instance, dendritic nanomedicine can cause permeability damage and cell membrane rupture. The pharmacological and toxicological analyses of nanomedicine have shown that once the particle size is reduced to a certain extent, the toxicity would increase dramatically.…”
Section: Not Applicable 4t1mentioning
confidence: 99%